2006
DOI: 10.1007/s10038-006-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the ABO blood group gene in three populations in the New Georgia group of the Solomon Islands

Abstract: To examine genetic affinity among Oceanian populations, polymorphisms of exons six and seven of the ABO blood group gene (ABO) were investigated in three populations-Munda town, Paradise village, and Rawaki village-in the New Georgia group of the Solomon Islands. The Munda and Paradise populations consist of Austronesian (AN)-speaking Melanesians; the Rawaki population consists of AN-speaking Micronesians who migrated from the Gilbert Islands to the New Georgia Islands approximately 30 years ago. We recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Our previous studies on the ABO gene and mtDNA polymorphisms suggested that an extensive gene flow occurred from Polynesian ancestors to indigenous Melanesians (Ohashi et al, 2004(Ohashi et al, , 2006b. Thus, a rapid expansion of Polynesian ancestors along the northern coast of New Guinea to Polynesia with negligible admixture with indigenous Melanesians, as hypothesized in the 'express train' model (Diamond, 1988;Bellwood, 1989), is not compatible with our previous observations.…”
Section: Introductioncontrasting
confidence: 69%
“…Our previous studies on the ABO gene and mtDNA polymorphisms suggested that an extensive gene flow occurred from Polynesian ancestors to indigenous Melanesians (Ohashi et al, 2004(Ohashi et al, , 2006b. Thus, a rapid expansion of Polynesian ancestors along the northern coast of New Guinea to Polynesia with negligible admixture with indigenous Melanesians, as hypothesized in the 'express train' model (Diamond, 1988;Bellwood, 1989), is not compatible with our previous observations.…”
Section: Introductioncontrasting
confidence: 69%
“…The reason why JPT and CHB were used rather than YRI or CEU was because Oceanic populations are genetically closer to JPT and CHB (East Asians) than to YRI (African) and CEU (European) populations. 24 No genes are located closely to ADRB2 and no SNPs outside the ADRB2 gene showed the strong LD with rs34623097. From this result, we conclude that rs34623097 is the primary polymorphism, in this genomic region, associated with obesity in the Oceanic populations.…”
Section: Resultsmentioning
confidence: 98%
“…Although Ravaki village is located in the Solomon Islands, the inhabitants had migrated there from the over-populated Gilbert Islands (Kiribati) in the 1960s in line with British governmental policy (Ohashi et al 2006). Therefore, Paradise and Munda represented the AN-speaking Melanesian population, Ha'apai and Nuku'alofa represented the AN-speaking Polynesian population, and Ravaki represented AN-speaking Micronesians (Table 1; Fig.…”
Section: Populationsmentioning
confidence: 96%